Perancangan Alat Pengaduk Dodol Ergonomis untuk Mengurangi Cedera pada Pekerja - Hidayatullah, Anung; Mauluddin, Yusuf; Rizki, Syahrul (Jurnal Kalibrasi, 2023)
PD Intan Bestory is a company engaged in the production of traditional food, namely dodol, by upholding traditional production methods that have been passed down from generation to generation. Among the various stages involved in making dodol, the kneading process plays a key role. However, this process has the potential for serious health risks for workers in the long term. Repetitive actions and excessive use of force in this process often result in various health problems, such as injuries to the hands, arms, wrists, feet and shoulders, which must be addressed. The aim of this research is to design an ergonomic dodol mixer to increase operator comfort during the mixing process and reduce the risk of injury. The method used in designing this tool is Ergonomic Function Deployment (EFD), which starts with an in-depth understanding of the operator's needs for the new tool and continues with anthropometric analysis to determine appropriate dimensions. Next, design evaluation was carried out using the Rapid Entire Body Assessment (REBA) method to assess the operator's posture while using the designed tool. It is hoped that dodol entrepreneurs can provide education to employees in operating tools to maximize function in supporting the production process. Using this tool will not only increase work comfort for employees, but also has the potential to increase overall productivity in the long term.